A statistical study of heterogeneous nucleation of ice by molecular dynamics - Bermúdez Di Lorenzo, Aleida J. (2015)
Abstract We studied the stochastic nature of heterogeneous nucleation of supercooled liquid water by molecular dynamics simulations. The systems were composed of 768 molecules; M of them had their positions restricted forming a solid nucleus (INM) for M = 48, 56, 64, 72, 80 and 90 molecules, and the rest were arranged in liquid state. By using a statistical analysis, we determined the nucleation rate (jM) for systems formed with IN64, IN72, IN80 and IN90. These results are coherent with the stochastic hypothesis for heterogeneous nucleation and show a direct relationship between M and jM.